Human Biomonitoring of Lead Exposure - Klotz, Katrin; Göen, Thomas (Metal ions in life sciences, 2017)
After a chronic exposure, lead accumulates in the human body, especially in bones and teeth. Critical effects of lead affect the nervous system, reproduction, fertility as well as genotoxicity and carcinogenicity [1]. Analyses of lead concentrations in human biological material are performed using inductively coupled plasma mass spectrometry and atomic absorption spectrometry, but also electrochemical methods and X-ray fluorescence spectroscopy. The predominant sample matrices include blood and bone, as well as urine, hair, nail, and saliva. To characterize first biological effects, diverse parameters are discussed as "biomarkers of effect". These include δ-aminolevulinic acid dehydratase (ALAD) and erythrocyte porphyrins (EPs) in blood as well as δ-aminolevulinic acid (ALA) in urine and plasma and coproporphyrin in urine. However, biomarkers of effect alone are not sufficiently sensitive for an early detection of a health impairment caused by lead. In summary, lead in blood is the most prominent and best validated biomarker for a lead exposure. A recommended diagnostic strategy for revealing lead-induced effects is the determination of lead in whole blood combined with the analysis of different effect parameters like ALA and coproporphyrin in urine and ALAD and zinc protoporphyrin (ZPP) in blood.
EVALuna2:35293